Analisis Penilaian Kualitas Jenis Pelayanan Tebaik dengan Metode Analytic Network Process (ANP) di Kantor Dinas Kependudukan dan Pencatatan Sipil Kota Pematangsiantar - Fajar Rudi Sartomo Samosir; Irfan Sudahri Damanik; Dedi Suhendro; Solikhun; Susiani (Puslitbang Sinergis Asa Professional, 2021)
This study aims to determine the best service quality at the Pematangsiantar City Population and Civil Registration Office, which includes services for making Identity Cards (KTP), Family Cards (KK), birth certificates, marriage certificates and receipt making. The method used in this research is the Analytic Network Process (ANP) method. The data collection technique used is a questionnaire technique that is distributed directly to the people who come to take care of the needs of personal and family data files. The parameters used consist of the facilities provided, employee behavior, services, and provisions. Determining community satisfaction with a service can be seen from the quality of the type of service. The results of this study were obtained in rank-1 with a normal value of 0.49126400, rank-2 family cards with a value of 0.18988000, rank-3 birth certificates with a value of 0.16073800, marriage certificates rank-4 with a value of 0.09707200 and Finally, rank-5 receipt services with a value of 0.06104600 With this research it is hoped that it can help the Pematangsiantar City Population and Civil Registration Service to evaluate the services provided to the community in order to meet community expectations in terms of managing the needs of personal and family data files and knowing the types of best services.